2014
DOI: 10.1016/j.ibmb.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of allatostatins in the regulation of juvenile hormone biosynthesis in the cockroach, Diploptera punctata

Abstract: The FGLamide allatostatins (FGL/ASTs) are a family of neuropeptides with pleiotropic functions, including the inhibition of juvenile hormone (JH) biosynthesis, vitellogenesis and muscle contraction. In the cockroach, Diploptera punctata, thirteen FGLa/ASTs and one allatostatin receptor (AstR) have been identified. However, the mode of action of ASTs in regulation of JH biosynthesis remains unclear. Here, we determined the tissue distribution of Dippu-AstR. And we expressed Dippu-AstR in vertebrate cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…AST-C inhibits JH synthesis by blocking the citrate carrier (CIC) that transports citrate from the mitochondria to the cytosol, obstructing the production of cytoplasmic acetyl-CoA that sustains JH synthesis in the CA of mosquitoes. Similar results were reported for the AST-A inhibition of JH synthesis in cockroaches [69]. Most studies on the activities of JH synthesis regulators have been done in vitro ; validation of these results in vivo will be facilitated by the development of CA-specific expression system that could enable a tissue-specific and time dependent manipulation of gene expression.…”
Section: Proteomics and Peptidomics Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…AST-C inhibits JH synthesis by blocking the citrate carrier (CIC) that transports citrate from the mitochondria to the cytosol, obstructing the production of cytoplasmic acetyl-CoA that sustains JH synthesis in the CA of mosquitoes. Similar results were reported for the AST-A inhibition of JH synthesis in cockroaches [69]. Most studies on the activities of JH synthesis regulators have been done in vitro ; validation of these results in vivo will be facilitated by the development of CA-specific expression system that could enable a tissue-specific and time dependent manipulation of gene expression.…”
Section: Proteomics and Peptidomics Studiessupporting
confidence: 75%
“…ODEs underscored that in the active CA enzymatic activities were not limiting [77]. Stimulation of JH synthesis with exogenous precursors has been reported for the CA of many insect species [68,69], and it seems that having an excess of enzymes is common in most insects studied.…”
Section: Metabolomics and Pathway Modelingmentioning
confidence: 99%
“…The fact that all the enzymes were fully functional revealed that in mosquitoes the Aea AST-C target is located before the entry of acetyl-CoA in the JH pathway. Recently, Huang et al (2014) showed that FGLamide AST inhibits JH III synthesis in D. punctata without modifying transcript levels of enzymes in the JH III biosynthetic pathway. The inhibitory effect was overridden by the addition of acetyl-CoA, mevalonate, diphosphomevalonate or farnesol, confirming that the effect is prior to the entry of precursors into the JH biosynthetic pathway (Huang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Huang et al (2014) showed that FGLamide AST inhibits JH III synthesis in D. punctata without modifying transcript levels of enzymes in the JH III biosynthetic pathway. The inhibitory effect was overridden by the addition of acetyl-CoA, mevalonate, diphosphomevalonate or farnesol, confirming that the effect is prior to the entry of precursors into the JH biosynthetic pathway (Huang et al, 2014). Our results exposed that FGLamide and PISCF ASTs may well have similar mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese hamster ovary (CHO) WTA11 (Euroscreen, Gosselies, Belgium) were cultured as described previously. 25 Transfections with pcDNA3.1D-Dippu-AstR or empty pcDNA3.1D vector (control) were carried out in T75 flasks at 60-80% confluency. After transfection, cells were incubated overnight and an additional 10 mL of culture medium was added.…”
Section: Functional Assay Of Astr In Response Of Ast Analoguesmentioning
confidence: 99%